2010
DOI: 10.1007/s00238-010-0466-9
|View full text |Cite|
|
Sign up to set email alerts
|

Perioperative fluid overload increases anastomosis thrombosis in the free TRAM flap used for breast reconstruction

Abstract: To increase perfusion pressure with vasoactive drugs may be in conflict with the opinion of the reconstructive surgeon who maintains that the systemic administration of vasoactive agents causes vasoconstriction of the pedicle artery and the microvasculature. In free flap surgery, deliberate fluid therapy is used with a minimum of vasoactive drugs. This retrospective study was performed to analyse the perioperative fluid therapy, its effect on hemodynamic parameters and on the outcome of free flap surgery. One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 16 publications
2
52
0
4
Order By: Relevance
“…[22][23][24][56][57][58] In a retrospective study of 104 free transverse rectus abdominis myocutaneous (TRAM) flaps, patients requiring flap revision because of anastomotic thrombosis had received significantly higher fluid volumes during the original operation. 57 High volumes of crystalloid administration, either greater than 130 ml/ kg per day or greater than 7 liters during surgery, have been associated with major medical and flap complications. 22,24 A retrospective review of 354 breast reconstructions indicated that crystalloid infusion rate is a significant independent predictor of complications.…”
Section: Fluid Administrationmentioning
confidence: 99%
“…[22][23][24][56][57][58] In a retrospective study of 104 free transverse rectus abdominis myocutaneous (TRAM) flaps, patients requiring flap revision because of anastomotic thrombosis had received significantly higher fluid volumes during the original operation. 57 High volumes of crystalloid administration, either greater than 130 ml/ kg per day or greater than 7 liters during surgery, have been associated with major medical and flap complications. 22,24 A retrospective review of 354 breast reconstructions indicated that crystalloid infusion rate is a significant independent predictor of complications.…”
Section: Fluid Administrationmentioning
confidence: 99%
“…These results bring question to the literature suggesting that patients at the upper extreme of resuscitation are at higher risk for complications in breast reconstruction. 7,8 In fact, it supports the opposite, that high normal fluid resuscitation rates may in fact protect against thrombotic events, and that it is really the low resuscitation rates that we must be concerned about. Higher rates of resuscitation may lead to an increased degree of hemodilution and increased blood velocity resulting in decreased viscosity.…”
Section: Discussionmentioning
confidence: 92%
“…11e14 Booi also suggested that higher fluid volumes were related to return to the OR for thrombus formation. 8 However, these studies tended to address total fluid volume or overall 24 h postoperative day zero resuscitation as opposed to intraoperative volume per kilogram per hour. Our current study provides more real-time information for the microsurgeon and anesthesiologist to potentially improve patient care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations